PERANCANGAN SISTEM INFORMASI BERBASIS WEB Studi Kasus: KSU BMT Al-Ikhwan Yogyakarta - Erwin Setiyawati; Sardiarinto Sardiarinto (LPPM Universitas Bina Sarana Informatika, 2016)
Abstract - The information is important for a company or enterprise in making decisions. The information system is expected to facilitate, promote and facilitate the performance of companies or enterprises to be more effective and efficient.Business Multipurpose Cooperative